Case Report: Retroperitoneal dedifferentiated solitary fibrous tumor with unexpected Pax-2 expression, mimicking high grade clear cell renal cell carcinoma - Wei, Jia; Yao, Chen-chen; Zou, Yue-Fen; Wei, Yong-Zhong; Fan, Qin-he; Gong, Qi-xing (Frontiers in Oncology, 2025)
Here, we report a case of retroperitoneal solitary fibrous tumor (SFT) in a 69-year-old Chinese woman. The patient had experienced lumbodorsal pain for more than two years. A computed tomography (CT) scan showed a mass adjacent to the right kidney, invading the surrounding soft tissues, measuring about 9.3 × 8.4 cm. An incision biopsy was performed. Microscopically, the tumor was composed of sheets of epithelioid cells with round to ovoid nuclei, and abundant clear cytoplasm. The cells showed severe nuclear atypia and brisk mitosis, with thin-walled branched blood vessels set against a myxoid to collagenous background. By immunohistochemistry, the tumor cells exhibited diffuse and strong expression of CK-pan, Pax-2, P53, INI-1 and H3K27me3. Staining for CD34, S100, SOX10, TLE1, WT-1, and CK5/6 was negative. STAT6 staining was weak and indistinct. Furthermore, next generation sequencing (NGS) disclosed a rare NAB2-STAT6 (N5::S16) gene fusion, accompanied by a C141G missense mutation of TP53 gene. Consequently, a diagnosis of dedifferentiated SFT (DSFT) was determined, rather than high-grade clear cell renal cell carcinoma. The case demonstrated that DSFTs are prone to be misdiagnosed, particularly in atypical locations with abnormal morphology and immunophenotypes. In such circumstances, a comprehensive evaluation of clinical, pathological, and imaging studies is essential, and molecular examinations can provide valuable diagnostic support.